2021
DOI: 10.1007/s12298-020-00923-x
|View full text |Cite
|
Sign up to set email alerts
|

Physio-chemical responses of exogenous calcium nanoparticle and putrescine polyamine in Saffron (Crocus sativus L.)

Abstract: The aim of this study was to investigate the effect of calcium nanoparticles (CaNP) and putrescine polyamine on some physiological and biochemical properties of saffron (Crocus sativus L.) under the control condition. Saffron corm was treated by different concentrations of putrescine (0, 0.25, 0.5, 1, 2 mM) and CaNP (0, 0.25, 0.5, 1, 1.5 g/l). The treatment of corm with putrescine and CaNP separately caused a significant increase in morphological parameters. Changes in biochemical parameters were also signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Ca NPs were also prepared and examined, found effective on crocin, picrocrocin, and safranal content [ 119 ]. Especially in combination with putrescine, Ca NPs could increase growth and phytochemical properties in Crocus sativus [ 119 ].…”
Section: Nano Activity-based Growth Promotersmentioning
confidence: 99%
See 1 more Smart Citation
“…Ca NPs were also prepared and examined, found effective on crocin, picrocrocin, and safranal content [ 119 ]. Especially in combination with putrescine, Ca NPs could increase growth and phytochemical properties in Crocus sativus [ 119 ].…”
Section: Nano Activity-based Growth Promotersmentioning
confidence: 99%
“…It was reported that Au NPs (20-22 nm) charged with harpin successfully induced defense responses in tobacco [118]. Ca NPs were also prepared and examined, found effective on crocin, picrocrocin, and safranal content [119]. Especially in combination with putrescine, Ca NPs could increase growth and phytochemical properties in Crocus sativus [119].…”
Section: Metal Nanoparticlesmentioning
confidence: 99%
“…In order to determine the values (values and uniformity of scales in digital layers of map information), methods based on fuzzy logic were used. The fuzzy set is a set that allows its members to have varying degrees of membership between 0 and 1 or 0 to 255 [19]. The fuzzy standardization method usually uses different functions, such as S-shaped, J-shaped, and linear functions for formatting.…”
Section: Areas Prone To Cultivating Saffron In Miyaneh Citymentioning
confidence: 99%
“…The previous research was done with Majlesi et al [73] indicated that stevioside and rebadioside content increased after synthesized AgNP treatment on stevia rebaudiosid plant. Different researches showed that metal nanoparticle separately or in the combination with other nanoparticles such as nanocomposites has ability of secondary metabolites induction like rosmarinic acid in Melissa officinalis [74], Saffron in Crocus sativus [75], steviosides and rebaudiosides in Stevia rebaudiana [76,77,78].…”
Section: Govorov and Carmelimentioning
confidence: 99%